Analysis of Procedural Errors in Arithmetic Problem Solving Through Polya Steps - Maulida, Dini Wardani; Mahmudah, Mutiara Hisda; Hidayati, Miftachul; Hidayati, Yulia Maftuhah (Universitas Wiralodra, 2025)
Difficulty is the cause of errors, math errors refer to actions or results that do not follow the correct steps or procedures in solving math problems. Therefore, the purpose of this study is to describe procedural errors in solving social arithmetic problems using Polya's steps. In this context, procedural errors refer to mistakes made by students while following the systematic steps recommended by Polya, which include understanding the problem, planning a solution strategy, carrying out the plan, and reviewing the results. This study aims to identify where and how errors occur at each of these stages, as well as to provide a deeper understanding of the challenges faced by students in solving social arithmetic problems. This research used a qualitative approach with a case study design. The participants of this study were 22 students of class VII of State Junior High School 3 Satu Atap Tawangharjo. Data validity uses triangulation of methods, namely through interviews and observations, and source triangulation. Data analysis technique with the flow method of the Miles and Huberman model. The study found that students experienced errors at each stage of Polya's steps. The percentage of student errors at each step is as follows: 20% in the understanding the problem step, 30% in the devising a plan step, 35% in the carrying out the plan step, and 15% in the looking back step. Three students were selected as samples, S-1, S-2, and S-3, each showing errors at different stages. S-1 made errors in understanding the problem and devising a plan, S-2 in devising a plan and carrying out the plan, while S-3 made errors in carrying out the plan and looking back. This research will describe the problem-solving errors experienced by students based on each Polya step they perform.